High Carbohydrate Diet Decreases Microbial Diversity and Increases Il-1β Levels in Mice Colon - Ulutas, Mehmet Sefa; Aydin, Erkin; Cebeci, Aysun (Korean Society Food Science & Technology-kosfost, 2024)
Western diet is known to contribute to intestinal dysbiosis and the progression of inflammation. Although the Turkish diet has different macronutrient contents, the intestinal inflammatory disease incidences in T & uuml;rkiye are comparable to Western countries. Thus, we hypothesized that high carbohydrate diets also contribute to inflammation of the colon. We compared diets with different macronutrient compositions and investigated their effects on colonic microbiota, cytokine, histology, and tight junction protein levels. High carbohydrate diet caused the lowest microbial diversity and is accompanied by the highest expression of interleukin-1 beta and claudin-1. A low carbohydrate diet with zero fiber resulted in the lowest inflammatory markers as well as the lowest occludin and claudin levels. Overall, our results indicate that carbohydrate and fiber contents of the diets are important contributors to colon health.
Aydin, Erkin/0000-0001-7811-2959;
Keywords: Inflammation; Microbiota; Tight Junction Protein; Carbohydrate; Dietary Fiber